Identifikasi Faktor Perubahan Bidang Tanah dalam Lingkup Administrasi Pertanahan dengan Pendekatan Sistem Informasi Geografis - Rendra, Mrabawani Insan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
This study aims to identify the factors influencing changes in land parcels related to land registration and land and building taxes. The methodology employed involves a spatial approach to changes in land parcels related to land administration, particularly land registration, and property taxes. The results indicated that the number of parcels changed is primary attributed to the division of joint rights, that used to known as